PENGARUH PROFITABILITAS DAN LIKUIDITAS TERHADAP NILAI PERUSAHAAN DENGAN STRUKTUR MODAL SEBAGAI VARIABEL INTERVENING (Studi pada Perusahaan Manufaktur yang terdaftar di Bursa Efek Indonesia Sektor Industri Barang Konsumsi Periode 2015-2019) - Falen Sadewo; Budi Santoso; I Nyoman Nugraha Ardana Putra (Master of Management, Mataram University, 2022)
This study aims to analyze the effect of profitability and liquidity on firm value through capital structure as an intervening variable in manufacturing companies in the consumer goods industry listed on the Indonesia Stock Exchange. This type of research is quantitative research. The sampling method used was purposive sampling method. Samples obtained as many as 28 companies from 2015 to 2019. To answer the hypothesis, this study uses multiple linear regression panel data which is analyzed using Eviews version 9 and path analysis. The result of this study shows profitability and capital structure have significant effect on firm value, while liquidty has no effect on firm value. Profitability has no effect on capital structure and liquidity affects capital structure. Furthermore, capital structure has not been able to mediate the effect of profitability on firm value. Capital structure is able to mediate the effect of liquidity on firm value. In allocating owned funds, it is necessary to be more careful in analyzing the performance of a company such as by looking at profitability, liquidity, capital structure to increase the expected value of the company.